The 2025 Gen Z Protest in Nepal: Media Representation and Discourse of Democratic Deficit - Bhusal, Purna Chandra; Khanal, Ananta (The Spectrum, 2026)
In this article, we analyze 15 media texts to examine how the 2025 Gen Z protest in Nepal has been represented across media over 10 days, from September 8-18, 2025. To that end, we applied theoretical concepts of media discourse and representation to examine media-constructed discourses about the Gen Z protest, conducting a qualitative analysis of media texts in three phases: In Vivo coding, patterning, and thematizing. During our analysis and interpretation of media texts, we identified three dominant themes: the Gen Z movement as a youth awakening, leadership crisis, and the critical lessons it teaches. Our interpretation and discussion of these themes indicated that the 2025 Gen Z movement was primarily driven by decades of unfulfilled promises of democratic leadership and that it has offered a historic opportunity for post-Gen Z protest political leaders to fulfill those deferred democratic promises. Hence, this article not only offers a critical analysis of the achievements and setbacks of the Gen Z protest but also strongly calls for rebuilding and reforming Nepal by incorporating the true democratic aspirations of the 2025 Gen Z movement.